Mortality and its predictors among patients with Guillain–Barré syndrome in the intensive care unit of a low-income country, Ethiopia: a multicenter retrospective cohort study - Bayu, Habtu Tsehayu; Demilie, Atalay Eshetie; Molla, Misganew Terefe; Kumie, Fantahun Tarekegn; Endeshaw, Amanuel Sisay (Frontiers in Neurology, 2024)
Background: Guillain-Barre syndrome is a rare autoimmune disease of the peripheral nervous system, in which there will be destruction of nerves involved in movement, transient pain, temperature, and touch sensations lead to muscle weakness, loss of sensation in the legs and/or arms, and problems swallowing or breathing. Published data on the outcomes of critical care for patients with GBS is extremely scarce in Africa, including Ethiopia. Therefore, this study aimed to assess mortality and its predictors among patients with GBS in the ICU of a low-income country, Ethiopia. Material and Methods: This retrospective cohort study was conducted at Tibebe Ghion Specialized Hospital and Felege Hiwot Comprehensive Specialized Hospital at Bahir Dar, Ethiopia, from January 1, 2019, to December 30, 2023. Data collection was conducted in the medical record rooms. Cox regression analysis was employed to identify predictors of mortality among GBS patients in the ICU. Bivariable and multivariable Cox regression models were fitted to compute crude and adjusted hazard ratios and 95% confidence intervals. A p-value of <0.05 was considered to indicate statistical significance. Results: Of 124 GBS patients admitted to the ICU, 120 patients included in the final analysis. During the follow-up, there were 23 (19.17%) deaths. The overall incidence rate of death was found to be 1.96 (95% CI: 1.30, 2.95). Deaths per 100 person-days observation. Traditional medicine (AHR=3.11, 95%: 1.12, 16.70), COVID-19 infection (AHR=5.44, 95% CI: 1.45, 73.33), pre-ICU cardiac arrest (AHR=6.44, 95% CI: 2.04, 84.50), and ICU readmission (AHR=4.24, 95% CI: 1.03, 69.84) were independent predictors for mortality Conclusion: Mortality among GBS patients admitted to ICU was high. Traditional medicine, COVID-19 infection, pre-ICU cardiac arrest, and readmission to the ICU were significant predictors of mortality. Large-scale studies with a prospective design would provide more robust evidence.